2016
DOI: 10.1155/2016/2492107
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa Relieves the Altered Insulin Receptor Signaling in Streptozotocin‐Induced Diabetic Rats Fed with a High‐Fat Diet

Abstract: The black cumin (Nigella sativa) “NS” or the black seeds have many pharmacological activities such as antioxidant, anticarcinogenic, antihypertensive, and antidiabetic properties. In this work, streptozotocin-induced diabetic rats fed with a high-fat diet were treated daily with NS oil (NSO) in order to study the effect on the blood glucose, lipid profile, oxidative stress parameters, and the gene expression of some insulin receptor-induced signaling molecules. This treatment was combined also with some drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 57 publications
7
33
0
Order By: Relevance
“…A possible role of the brain insulin resistance and a reduced insulin signaling in the AD's pathogenesis, was also described by several studies (Aliev et al, 2014 ). Baalba et al, by using streptozotocin-induced diabetic (STZ-T2DM) rats, showed that the daily intake of NSO induced the expression of insulin receptor and altered the expression of insulin-like growth factor-1 and phosphoinositide-3 kinase (Balbaa et al, 2016 ). Based on these results, subsequently, the authors showed that in STZ-T2DM rats, NSO (2.0 ml/Kg) and anti-diabetic drugs (metformin and glimepiride) alone and/or in combination, were able to suppress brain levels of oxidative stress markers such as xanthine oxidase (XO) and NOS, through the product of lipid peroxidation [e.g., thiobarbituric acid reactive substances (TBARS)] (Balbaa et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…A possible role of the brain insulin resistance and a reduced insulin signaling in the AD's pathogenesis, was also described by several studies (Aliev et al, 2014 ). Baalba et al, by using streptozotocin-induced diabetic (STZ-T2DM) rats, showed that the daily intake of NSO induced the expression of insulin receptor and altered the expression of insulin-like growth factor-1 and phosphoinositide-3 kinase (Balbaa et al, 2016 ). Based on these results, subsequently, the authors showed that in STZ-T2DM rats, NSO (2.0 ml/Kg) and anti-diabetic drugs (metformin and glimepiride) alone and/or in combination, were able to suppress brain levels of oxidative stress markers such as xanthine oxidase (XO) and NOS, through the product of lipid peroxidation [e.g., thiobarbituric acid reactive substances (TBARS)] (Balbaa et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the fenugreek seeds [34], Marrubium vulgare [35], N. sativa [36], A. sativum [37], Carum carvi, and Ziziphus lotus [38,39] shows an antidiabetic effects in streptozotocininduced diabetic in rat and alloxan-induced diabetes in mice. Khan et al demonstrated in vitro that P. dactylifera seeds extract inhibit α-glucosidase and α-amylase level [40].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of diabetes was ascertained after 48 h post-STZ injection by determination of blood glucose level. The animals that possessed blood glucose values of over 250 mg/dL were supposed to be diabetic [ 25 ].…”
Section: Methodsmentioning
confidence: 99%